Examining the experiences of students, teachers and leaders at Educate Together second-level schools - Georgiana Mihut; Selina MacCoy (The Economic and Social Research Institute (ESRI), 2020)
The report being launched at an online research seminar today, is based on a mixed methods research study conducted at 11 ETSS late in 2019, prior to the COVID-19 school closures. The research involved students, teachers, parents, school leaders and other stakeholders.
Keywords: 330